KARSTIC LANDSCAPE STUDY BASED ON REMOTE SENSING DATA: THE CASE OF KSIROMERO REGION, AITOLOAKARNANIA - WESTERN GREECE - Golubović Deliganni, M.; Parcharidis, I.; Pavlopoulos, K. (Bulletin of the Geological Society of Greece, 2010)
The aim of this study is to investigate and recognize karst landforms in the area of Ksiromero (Aitoloakarnania, Western Greece) based on medium resolution remote sensing data. In order to highlight karstic structures appropriate and innovative methodologies of image analysis have been developed, applied and compared. In particular, the original Landsat 5 TM bands have been, first, ad-hoc stretched and then processed to obtain the so-called Tasseled Cap Features and the Principal Component images. Finally, a comparative study between the two methods has been carried out.